Water Intake, Body Water Regulation and Health - Adams, William M. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The purpose of this Special Issue, "Water Intake, Body Water Regulation, and Health", is to present novel reviews and experimental data regarding hydration physiology and its implication in overall health. Water has previously been dubbed the forgotten nutrient due to humans' and animals' ability to subsist seemingly unchanged across a wide range of daily water intakes. However, with the introduction of stressors such as exercise, diseased states, and/or chronic high or low water intake, the homeostatic signals related to body water regulation can influence organ and whole-body health. This Special Issue will discuss water intake, the scientific rationale surrounding the U.S. and European water intake guidelines, homeostatic mechanisms, diseases related to dysfunction of water regulation, and differences in the volume and the vehicle in which the water is contained (i.e., plain water versus mixed beverages) on water intake during and following exercise. The aim is to continue discussion surrounding water, the previously forgotten nutrient, and highlight the importance of water in daily life.